Variação estrutural quantitativa do lenho de apeiba echinata gaerth.- tiliaceae - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2005)
The studies of variability in the dimensions of xylematic elements have been carried out for a long time in temperate species. However, studies of the variation in the dimensions of vessel elements, fibers and rays, in the axial direction (base-apex) and radial direction (medulla-exchange), along the stem of species that develop in tropical climate forests are still few in relation to those of temperate species. The wood, for presenting a complex biological system, has a great anatomical variability. These variations in the cambium probably occur during the aging of the wood and modifications imposed by environmental conditions. The present work is a contribution to the anatomical knowledge of the wood of Apeiba echinata Gaerth. For this purpose, wood discs were removed along the stem, from which test bodies were obtained every 2 cm, in the pith - cambium direction. For a quantitative analysis of the wood, permanent and temporary slides were prepared, where measurements are being made. Through these measurements it is hoped to observe that the variables analyzed follow a defined pattern of variation. According to anatomists, there may be an influence of the age of the vascular cambium on the structure of the wood. The authors say that the cambium can present periods of juvenility, maturity and senescence, but warn that in some species the duration of these periods is difficult to be defined.
Quantitative structural variation of the wood of apeiba echinata gaerth - tiliaceae
Keywords: Apeiba echinata gaerth; Tiliaceae; Lenha; CNPQ::CIENCIAS BIOLOGICAS::BOTANICA